Kualitas Informasi Sebagai Determinan Kepuasan Pengguna Website Lembaga Legislatif: Perspektif Webqual 4.0 Pada DPRD Toraja Utara - Gidion A.N. Pongdatu; Ferayanti B. Gallaran; Intan S.D. Welem (Bajang Institute, 2026)
Regional legislative websites serve as a key channel for information transparency and public participation, yet their usefulness largely depends on perceived content quality. This study seeks to identify which dimension most strongly determines user satisfaction with the North Toraja DPRD website by applying the WebQual 4.0 framework. The influence of three constructs on user satisfaction was examined: information quality, usability, and service interaction quality. Respondents comprised 58 individuals who had visited the website, recruited purposively and measured through a 1–5 Likert-scale questionnaire. Data were analyzed using multiple linear regression after the instrument was established as valid (all items r > 0.2586) and reliable (Cronbach's alpha between 0.801 and 0.885). The regression model accounted for 85.3% of the variance in user satisfaction (R² = 0.8525; F(3,54) = 104.03; p < 0.001). All predictors were significant, with information quality emerging as the strongest driver (β = 0.577; p < 0.001), followed by service interaction quality (β = 0.273; p = 0.021) and usability (β = 0.268; p = 0.035). A comparison of standardized coefficients showed that the contribution of information quality (0.535) exceeded more than double that of service interaction quality (0.237) and usability (0.207). Content is therefore the central axis of user satisfaction, suggesting that management should prioritize information timeliness and accuracy while improving access stability and navigation. The moderately high inter-predictor correlation (0.79–0.83) is reported transparently so that results are interpreted with caution. This research adds to the limited application of WebQual 4.0 to regional legislative websites.